Atmospheric corrosion patterns of electrogalvanized mild steel at east southern coastal areas of CPEC. Issue 12 (14th June 2018) - Jamil, Ishrat; Bano, Humaira; Castano, Juan G.; Mahmood, Azhar; Zafar, Faiza
Abstract : The primary goal of the study was to establish corrosivity category in accordance with ISO 9223 norm of the two test stations located at National Institute of Oceanography (NIO) and Karachi Port Trust (KPT) along the east southern coastal route of China Pakistan Economic Corridor (CPEC) project in Pakistan. Electrogalvanized mild steel test coupons were exposed for a period of 12 months from May 2014 to May 2015. Results indicated that for both NIO and KPT test stations the corrosivity category in term of corrosion rate (C5+) was not in agreement with the corrosivity category (C5) established by using the pollution category and time of wetness. Corrosion kinetic parameters n and correlation coefficient (R 2 ) obtained for NIO were 1.58 and 0.98 and for KPT 1.43 and 0.95 respectively. Scanning electron microscopy/energy dispersive X‐ray spectroscopy (SEM/EDS) showed the presence of simonkolleite at NIO while zincite and hydrozincite at KPT. Fourier transform infrared (FTIR) spectroscopy showed that the typical corrosion products formed on both test stations were simonkolleite and hydrozincite. XRD showed the presence of zincite at both test stations and hydrozincite only at KPT. Abstract : The primary goal of the study was to establish corrosivity category in accordance with ISO 9223 norm of the two test stations located at National Institute of Oceanography (NIO) and Karachi Port Trust (KPT) along the east southern coastal route of China Pakistan Economic Corridor (CPEC) project in Pakistan. Electrogalvanized mild steel test coupons were exposed for a period of 12 months from May 2014 to May 2015.